Extraction and recovery of phytochemical components and antioxidative properties in fruit parts of Dacryodes rostrata influenced by different solvents - Thavamoney, Nisha; Sivanadian, Leykkha; Tee, Lee Hong; Khoo, Hock Eng; Prasad, Krishnamurthy Nagendra; Kong, Kin Weng (Springer Verlag (Germany), 2018)
This study investigated the recovery of phytochemical antioxidants in Dacryodes rostrata fruit using different extraction solvents. The effects of solvent of varying polarities with sequential extraction method on the recovery of phenolics, flavonoids, carotenoids and anthocyanins from different parts of the fruit (seed, pulp and peel) were determined. Their antioxidant activities were further determined using DPPH radical, ferric reducing antioxidant power (FRAP), hydroxyl radical scavenging, superoxide anion radical scavenging and phosphomolybdenum method. Dacryodes Rostrata seed had the highest total phenolic content with 50% ethanol as the most efficient extraction solvent. The highest total flavonoid content was obtained in ethyl acetate extract of fruit pulp, whereas peel extracted with hexane and 50% ethanol was the highest in total carotenoid content and total anthocyanin content, respectively. The seed extracted with 50% ethanol exhibited the strongest DPPH radical scavenging activity. Iron chelating activity measured by FRAP assay was the best in seed extracts, particularly in those polar extracts derived from water and 50% ethanol. Antioxidant activities of 50% ethanol extract of D. rostrata seed was the highest when determined by FRAP and phosphomolydenum assays. However, the influence of extraction solvents is not distinctly shown by hydroxyl radical and superoxide anion radical scavenging activities. This is the first report on the effect of various extraction solvents on the recovery of phytochemicals in D. rostrata fruit parts and the seed of D. rostrata is a potential source of polar antioxidants.